Increased root herbivory under elevated atmospheric carbon dioxide concentrations is reversed by silicon-based plant defences - Frew, Adam; Allsopp, Peter G.; Gherlenda, Andrew N.; Johnson, Scott N. (The Journal of applied ecology, 2017)
1. Predicted increases in atmospheric concentrations of CO₂ may alter the susceptibility of many plants to insect herbivores due to changes in plant nutrition and defences. Silicon plays a critical role in plant defence against herbivores, so increasing such silicon-based defences in plants may help remediate situations where plants become more susceptible to herbivores. 2. Sugar cane (Saccharum spp. hybrid) was subjected to fully factorial treatment combinations of ambient (aCO₂) or elevated (eCO₂) atmospheric CO₂ concentrations; ambient silicon or silicon supplementation; insect-free or subject to root herbivory by greyback canegrub (Dermolepida albohir tum). A glasshouse study was used to determine how these factors affected rates of photosynthesis, growth, chemistry (concentrations of silicon, carbon, nitrogen and non-structural carbohydrates). Changes in canegrub mass were determined in the glasshouse pot study, together with more detailed assessment of how eCO₂ and silicon supplementation affected performance and feeding behaviour (relative growth rate and relative consumption) in a 24-h feeding efficiency assay. 3. Elevated CO₂ and silicon supplementation increased rates of photosynthesis (+ 32% and 14%, respectively) and sugar cane biomass (+ 45% and 69%, respectively). Silicon supplementation increased silicon concentrations in both leaves and roots by 54% and 75%, respectively. eCO₂ caused root C : N to increase by 12%. 4. Canegrub performance and consumption increased under eCO₂; relative growth rate (RGR) increased by 116% and consumed 57% more root material (suggestive of compensatory feeding). Silicon application reversed these effects, with large decreases in mass change, RGR and root consumption (65% less root mass consumed). 5. Synthesis and applications. Our results suggest future atmospheric carbon dioxide concentrations could lead to increased crop damage by a below-ground herbivore. Increasing bioavailable silicon in soil stimulated silicon-based defences which dramatically decreased herbivory and herbivore performance. Our findings suggest future pest management strategies could benefit from characterising deficiencies in bioavailable silicon in agricultural soils and targeted application of silicon fertilisers. Moreover, future breeding programmes should exploit variation in silicon uptake between cultivars to enhance silicon uptake in new crop varieties. Silicon-based plant defence proved to be highly beneficial for remediating the negative effects of atmospheric change on sugar cane susceptibility to herbivory and could be applicable in other crops.